An orange pigment from the marine bacterium Paracoccus haeundaensis SAB E11 as a prospective source of natural antioxidants (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Abubakar H, Astuti RI, Listyowati S, Batubara I, Wahyudi AT. 2022. An orange pigment from the marine bacterium Paracoccus haeundaensis SAB E11 as a prospective source of natural antioxidants. Biodiversitas 23: 4730-4737. Bacterial pigment extracts are the source of many natural antioxidant substances. The present study aimed to assess the antioxidant activity of an orange pigment derived from a marine bacterium, identified as Paracoccus haeundaensis SAB E11, analyzed by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azino-bis(ethylbenzothiazoline-6-sulfonic acid) (ABTS). Methanol-pigmented crude extract of P. haeundaensis SAB E11 exhibited the best DPPH scavenging activity with an IC50 value of 54.7 mg/mL, while the n-hexane crude pigment extract of the bacterium reduced ABTS optimally with an IC50 value of 24.46 mg/mL. The analysis of antioxidant compounds in P. haeundaensis SAB E11 was identified by combining liquid chromatography with tandem mass spectrometry (LCMS/MS). The five antioxidant compounds from methanol and n-hexane crude pigment extract of P. haeundaensis SAB E11 have been detected. Polyphenols were found to be the major compound, such as 3,5,3’,4’-tetrahydroxystilbene, scopoletin, and liquiritigenin. The other compounds were dihydroactinidiolide (terpenes) and ricinoleic acid (a fatty acid compound). The orange-colored extract of marine bacterium P. haeundaensis SAB E11 could be promising pharmacological capabilities as an antioxidant.
Keywords: ABTS, antioxidant, DPPH, marine bacterium, pigment extract